Contemporary pedagogy? The use of theory in practice: An evidence-informed perspective - Taylor, Robin D.; Taylor, Jamie; Ashford, Michael; Collins, Rosie (Frontiers in Sports and Active Living, 2023)
Utilizing cognitive psychology as a foundation, this paper offers a deeper consideration of contemporary theoretical influences on coaching pedagogy. Countering recent dichotomies between pedagogic approaches, we reintroduce key findings from the cognitive tradition and their implications for practice which coaches may find useful. Using cognitive load, novice and expert differences, desirable difficulty, and fidelity, we suggest that the lines drawn between different ‘pedagogies’ may not be as sharp as suggested. Instead, we suggest that coaches avoid defining themselves as being aligned to a specific pedagogical stance. We conclude by advocating for research informed practice, absent of strict theoretical boundaries and instead, considering contemporary pedagogy as drawing on the needs of the context, the experience of the coach and the best available evidence.